Spain : Safety Net, Bank Resolution, and Crisis Management Framework: Technical Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This technical note examines the safety net, bank resolution, and crisis management framework in Spain. The financial safety net architecture for the banking sector comprises the Banco de Espana (BdE), the Fondo de Garantia de Depositos (FGD), and the Fondo de Reestructuracion Ordenada Bancaria (FROB). The note discusses that institutional roles and instruments of the FROB and the FGD need to be realigned. Given the current crisis, authorities should make it a key priority to promptly improve the tools to resolve banks in line with recent international practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet